The enzyme reference : a comprehensive guidebook to enzyme nomenclature, reactions, and methods - Purich, Daniel L; Allison, R. Donald (Academic Press, 2002)
The aim of this work is to provide a fuller spectrum of information in a single source on enzyme-catalyzed reactions than is currently available in any published reference work or as part of any Internet database. The Enzyme Reference: A Comprehensive Guidebook to Enzyme Nomenclature, Reactions, and Methods includes 20,000 review articles and seminal research papers. Additionally, it provides a novel treatment of so-called ATPase and GTPase reactions to account for the noncovalent substratelike and productlike states of molecular motors, elongation factors, transporters, DNA helicases, G-reulatory proteins, and other energases. Key Fetures* Includes a compendium of over 6,000 enzyme reactions (including enzyme commission numbers, alternative names, substrates, products, alternative substrates, and properties) * Covers over 900 chemical structures of key metabolites and cofactors* Index directs readers to the exact pages for over 9,500 enzyme names
Keywords: biochemie; enzymy; Enzymes